A NEW OIL PIPELINE CORROSION PREDICTION MODEL USING ENHANCED ASSOCIATIVE CLASSIFICATION - TONG , HAN CHERN (2018)
Pipeline leakages occur quite frequently and most of the time they are the source of damage. Leakage does not only cause the loss of assets, but it may be both polluting and life-threatening. In order to tackle the dilemma, experts conduct experiments to analyze the source of the leakage.